The effects of different activating agents on the physical and electrochemical properties of activated carbon electrodes fabricated from wood-dust of Shorea robusta. Issue 9 (September 2021) - Shrestha, D.; Rajbhandari, A.
Abstract: This study focuses on the effects of activating agents on the physical and electrochemical properties of activated carbon (AC) electrodes, fabricated from wood dust of Shorea robusta . Three different activating agents namely H3 PO4, KOH and Na2 CO3 have been used to prepare ACs, which were named as: Sr–H3 PO4, Sr–KOH and Sr–Na2 CO3 . The ACs were characterized by TGA/DSC, XRD, Raman, SEM, FTIR and BET. All the as prepared ACs were found to be amorphous in nature. The oxygen surface functionality was developed at the surface. The surface area of Sr–H3 PO4, Sr–KOH and Sr–Na2 CO3 were found to be 1269.5 m 2 /g, 280.6 m 2 /g and 58.9 m 2 /g respectively. The activated carbon-electrodes were then fabricated and supercapacitive performances were evaluated by "three electrode system" in aqueous 6M KOH using cyclic voltammetry (CV), galvanostatic charge discharge (GCD) and electrochemical impedance spectroscopy (EIS).The GCD performed at 1A/g revealed the specific capacitance values were 136.3 F/g, 42.2 F/g and 59.1 F/g for Sr–H3 PO4, Sr–KOH and Sr–Na2 CO3 -electrodes, respectively. Energy density for Sr–H3 PO4 electrode was found to be 3.0 Wh/kg at 99.6 W/kg power densities. Moreover, it also displayed imposing cyclic stability of about 96.9 %, 89.5 % and 78.5 % after 1000 cycles of charge/discharge respectively. The overall electrochemical performance of Sr–H3 PO4 showed outstanding supercapacitive performances demonstrating the high possibility of this material to be used for the EDLC application in supercapacitive energy storage. The Nyquist plot also showed the lowest internal resistance of about 0.4 Ω for Sr–H3 PO4 electrode. Abstract : Shorea robusta ; Specific capacitance; Energy density; Power density, Cyclic stability.